IMPLEMENTASI KEBIJAKAN PERATURAN BUPATI NO 15 TAHUN 2019 TENTANG PERCEPATAN PENCEGAHAN STUNTING TERINTEGRASI DI KABUPATEN PROBOLINGGO - Yuliati, Evi; Natsir, Mohammad (MAP (Jurnal Manajemen dan Administrasi Publik), 2024)
This research explains the coordination of the stunting prevention team in efforts to accelerate the reduction and prevention of stunting in Probolinggo Regency. Currently, Probolinggo Regency is one of the districts in Indonesia with a high prevalence rate of stunting in toddlers. The theory of effective coordination techniques is used as a reference or guidance in this research. The research results show that coordination in accelerating the reduction and prevention of stunting in Probolinggo Regency does not fully meet effective coordination techniques. This is because there is no clear and detailed division of tasks and responsibilities between the agencies involved, there are frequent changes in membership, especially in strategic positions in the Probolinggo Regency stunting prevention team due to mutations, there is no written standard operating procedure that is used as a joint guidelines, management of stunting data that is not yet optimal and integrated, active participation of members in the implementation of coordination meetings is still lacking, and leadership by the team leader is not yet effective in coordinating and controlling the implementation of accelerated reduction and prevention of stunting in Probolinggo Regency.